Dental curable calcium phosphate cement
Patent Information
- Application Number
- JP2022105142
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-06-29
AI Technical Summary
Conventional calcium phosphate cements are ineffective in restoring mineral density to demineralized dentin, particularly in areas with early root caries, and do not adequately seal dentinal tubules, leading to issues like root caries and hypersensitivity.
A dental hardening calcium phosphate cement composed of a powder and liquid mixture, containing specific calcium phosphate compounds, fluoride salts, polyvalent organic acids, and water, with a controlled particle size distribution, that seals dentinal tubules and promotes mineral density recovery by precipitating hydroxyapatite deep within the tubules.
The cement effectively seals dentinal tubules and restores mineral density to demineralized dentin, providing enhanced protection against root caries and hypersensitivity.
Abstract
Description
[Technical field]
[0001] The present invention relates to a hardenable dental calcium phosphate cement. [Background technology]
[0002] Due to the so-called 8020 movement (improvement of oral hygiene, preservation of tooth structure (MI: Minimal Intervention)), which encourages people to keep more than 20 of their own teeth even at the age of 80, the rate at which the elderly retain their teeth has increased dramatically. However, this has also given rise to the problem of exposed dentin due to new dental diseases (tooth wear, loss of alveolar bone due to periodontal disease, etc.). Unlike enamel, exposed dentin has a low mineral concentration in the tissues that make up dentin, so it does not have good caries resistance. In addition, the dentinal tubules, which are about 1 μm to 3 μm in diameter, can open up due to the action of acids in the mouth, causing dentin hypersensitivity.
[0003] As a method to improve this, a method of covering the dentinal tubules with a polymer-based material and a method of sealing the dentinal tubules by alternately applying two types of materials to precipitate inorganic salts and form a physical barrier are known. However, these methods only cover the shallow parts and surfaces near the openings of the dentinal tubules, and there is a problem that they are easily destroyed by abrasion with a toothbrush, etc. In addition, even though the material is highly biocompatible, there is a problem that plaque adheres to the material when it is applied, causing inflammation or root caries.
[0004] On the other hand, calcium phosphate cement, which is a combination of tetracalcium phosphate and anhydrous calcium hydrogen phosphate, is known as a hardenable calcium phosphate composition. It is bioabsorbable hydroxyapatite (Ca 10It is said that it gradually converts to (PO4)6(OH)2) and can further integrate with biological hard tissues while maintaining its shape. As an example of using such calcium phosphate cement to seal dentinal tubules, Patent Document 1 discloses a dentin remineralization agent containing a specific amount of an alkali metal salt of phosphoric acid relative to tetracalcium phosphate particles, and describes that a dense hydroxyapatite layer is formed on the dentin surface and hydroxyapatite is precipitated deep within the dentinal tubules, thereby sealing the dentinal tubules.
[0005] Furthermore, Patent Document 1 discloses a calcium phosphate cement containing a fluoride compound, and describes that the inclusion of a fluoride compound provides acid resistance to the tooth structure and promotes calcification. Sodium fluoride is used as a specific fluoride compound, and it is suggested that the acid resistance is provided to the tooth structure by the formation of fluoroapatite.
[0006] Furthermore, Patent Document 1 specifically describes the effect of improving the sealing ability of dentinal tubules even in deep parts of the dentinal tubules by adding disodium monohydrogen phosphate (Na2HPO4) as an alkali metal salt of phosphoric acid.
[0007] Furthermore, Patent Document 2 also proposes a calcium phosphate cement. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2010 / 113800 [Patent Document 2] Japanese Patent Application Publication No. 06-321515 Summary of the Invention [Problem to be solved by the invention]
[0009] However, as described below, the inventors have conducted research and found that when conventional calcium phosphate cements are used on demineralized dentin (hereinafter also referred to as "demineralized dentin") with low mineral density, such as in areas of early root caries, the recovery rate of mineral density is low, leaving room for improvement in effectiveness when used as an early root caries inhibitor.
[0010] The gums may recede due to aging, periodontal disease, etc., and the roots of teeth that were previously covered by the gums may become exposed in the oral cavity. Unlike the crowns of teeth, which have thick enamel, the dentin at the roots is not covered by enamel. Dentin has a countless tubule structure and contains a large amount of organic layers, mainly collagen, so its mineral density is low at about 50%, and it is physically and chemically weaker than enamel, which has a mineral density of about 97%. Therefore, caries is likely to occur at the roots of teeth exposed in the oral cavity. Here, "caries" refers to substantial loss of teeth caused by demineralization (elution of mineral components) of enamel and dentin by acids produced by bacteria in the oral cavity metabolizing carbohydrates. Among caries, dentin caries that occurs at the roots of teeth is called "root caries".
[0011] In root caries, the dentin exposed through receding gums is in a demineralized state, with lower mineral density, due to minerals being dissolved by acids produced by microorganisms in the oral cavity. Even if conventional calcium phosphate cements are used on demineralized dentin, which is in a state of lower mineral density, sufficient mineral density cannot be restored, making it difficult to inhibit or treat early stages of root caries.
[0012] As described above, when conventional calcium phosphate cements are applied to an area of early stage root caries, it is difficult to inhibit or treat the early stage caries due to the location of the root surface.
[0013] Furthermore, Patent Documents 1 and 2 do not disclose the ability to restore mineral density in demineralized dentin, nor do they disclose any problems that may arise when used on demineralized dentin in root caries.
[0014] The present invention has been made to solve the above-mentioned problems, and has an object to provide a dental hardenable calcium phosphate cement that has excellent sealing properties for dentinal tubules and also has excellent ability to restore mineral density even in demineralized dentin with low mineral density. [Means for solving the problem]
[0015] As a result of extensive investigations, the present inventors discovered that a dental composition having a specific composition can solve the above problems, and after further investigations they have completed the present invention.
[0016] That is, the present invention includes the following inventions. [1] It is composed of a first material which is a powder and a second material which is a liquid. The first material includes a calcium phosphate compound (A), a fluoride salt of a divalent or higher cation (B), and a polyvalent organic acid (C) that forms an insoluble salt with the divalent or higher cation; The second material contains water (D), A dental hardenable calcium phosphate cement, in which the cumulative frequency of particle diameters of 0 μm or more and 3 μm or less in a volume-based cumulative particle diameter distribution is 3% or more in the total amount of the fluoride salt of a divalent or higher cation (B). [2] The dental hardenable calcium phosphate cement according to [1], wherein the fluoride salt (B) is zinc fluoride and strontium fluoride. [3] The dental hardenable calcium phosphate cement according to [1] or [2], wherein the polyvalent organic acid (C) that forms an insoluble salt with the divalent or higher cation is at least one selected from the group consisting of tannic acid, catechol, tiron monohydrate, protocatechuic acid, protocatechuic acid esters, pyrocatechol, pyrogallol, shikimic acid, gallic acid esters, and catechin. [4] The dental hardenable calcium phosphate cement according to any one of [1] to [3], wherein the average particle size of the fluoride salt of a divalent or higher cation (B) is less than 34 μm. [5] The dental hardenable calcium phosphate cement according to any one of [1] to [4], wherein the calcium phosphate compound (A) comprises at least one selected from the group consisting of tetracalcium phosphate, anhydrous calcium hydrogen phosphate (CaHPO4), anhydrous calcium dihydrogen phosphate (Ca(H2PO4)2), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), amorphous calcium phosphate (Ca3(PO4)2·nH2O), calcium pyrophosphate (CaH2P2O7), octacalcium phosphate (Ca8H2(PO4)6·5H2O), calcium hydrogen phosphate dihydrate (CaHPO4·2H2O), and calcium dihydrogen phosphate monohydrate (Ca(H2PO4)2·H2O). [6] The dental hardenable calcium phosphate cement according to any one of [1] to [5], wherein the first material or the second material further contains a pH adjuster. [7] The dental hardenable calcium phosphate cement according to [6], wherein the pH adjuster is an alkali metal salt of phosphoric acid. [8] The dental hardenable calcium phosphate cement according to any one of [1] to [7], wherein the first material or the second material further contains an inorganic filler. [9] The dental hardenable calcium phosphate cement according to [8], wherein the inorganic filler comprises at least one selected from the group consisting of light anhydrous silicic acid and metal oxides.
[10] The dental hardenable calcium phosphate cement according to any one of [1] to [9], wherein the second material further contains an antibacterial agent.
[11] The dental hardenable calcium phosphate cement according to any one of [1] to
[10] , wherein the calcium phosphate compound (A) is in the form of particles having an average particle size of 0.1 to 40 μm.
[12] The dental hardenable calcium phosphate cement according to any one of [1] to
[11] , wherein the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation is in the form of particles and has an average particle size of 5.0 to 100 μm.
[13] A tooth surface treatment material comprising the dental hardenable calcium phosphate cement according to any one of [1] to
[12] .
[14] A material for suppressing dentin hypersensitivity, comprising a dental hardenable calcium phosphate cement according to any one of [1] to
[12] .
[15] A toothpaste comprising the dental hardenable calcium phosphate cement according to any one of [1] to
[12] .
[16] A root caries treatment material comprising a dental hardenable calcium phosphate cement according to any one of [1] to
[12] . Effect of the Invention
[0017] According to the present invention, it is possible to provide a dental hardenable calcium phosphate cement which is excellent in sealing dentinal tubules and also has an excellent ability to restore mineral density even in demineralized dentin having low mineral density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. The dental hardenable calcium phosphate cement of the present invention is composed of a first material which is a powder and a second material which is a liquid, the first material containing a calcium phosphate compound (A), a fluoride salt (B) of a divalent or higher cation (hereinafter also referred to as "fluoride salt (B)"), and a polyvalent organic acid (C) which forms an insoluble salt with a divalent or higher cation (hereinafter also referred to as "polyvalent organic acid (C)"), the second material containing water (D), and the cumulative frequency of particle diameters of 0 μm or more and 3 μm or less in a volume-based cumulative particle diameter distribution is 3% or more in the total amount of the fluoride salt (B) of a divalent or higher cation.
[0019] By using the above-mentioned composition, a dental hardenable calcium phosphate cement is obtained which is excellent in sealing dentinal tubules and is also excellent in restoring the mineral density even to demineralized dentin having a low mineral density.
[0020] In this specification, the upper and lower limit values of the numerical ranges (content of each component, average particle size, etc.) can be appropriately combined.
[0021] Although the present invention is not limited thereto, the reason why the above-mentioned excellent effects are exhibited is considered to be as follows. First, the calcium phosphate compound (A) and the fluoride salt of divalent or higher cations (B) having a particle size of about 3 μm or less in the particle size distribution are allowed to penetrate into the "dentinal tubules" having a diameter of about 1 to 3 μm present in dentin as particles, and the polyvalent organic acid (C) is allowed to penetrate as a solution in water, thereby sealing the dentinal tubules and promoting the recovery of mineral density. Note that even if the polyvalent organic acid (C) is in the form of particles, a more excellent effect can be obtained by allowing it to penetrate into the dentinal tubules.
[0022] More specifically, a paste obtained by mixing a first material (hereinafter also referred to as "powder material") containing a calcium phosphate compound (A), a fluoride salt (B), and a polyvalent organic acid (C) with a second material (hereinafter also referred to as "liquid material") containing water (D) is applied to an affected area (e.g., demineralized dentin), whereby calcium phosphate compound (A) and fluoride salt (B) whose particle size in the particle size distribution is about 3 μm or less penetrate into the dentinal tubules in the form of particles. At the same time, a part of the polyvalent organic acid (C) dissolved by mixing with water (D) also penetrates into the dentinal tubules. At this time, since the surface layer of the polyvalent organic acid (C) is dissolved in the water (D), the polyvalent organic acid (C) in the form of particles with a smaller particle size may also penetrate into the dentinal tubules, in which case both the dissolved polyvalent organic acid (C) and the polyvalent organic acid (C) in the form of particles act to obtain a more excellent effect.
[0023] From the particles that remain within the dentinal tubules, calcium ions, phosphate ions, fluoride ions, divalent or higher cations (divalent or higher metal ions) (such as zinc), and polyvalent organic acids (C) (such as tannic acid), which are essential components for mineral density recovery, are dissolved into the interior of the dentinal tubules and become present inside the dentinal tubules. As a result, these components work together to restore the mineral density of the dentin surrounding the dentinal tubules (especially dentin that has been softened by demineralization due to early caries, etc.). Here, it is considered important that the presence of polyvalent organic acids (C) in particular re-crosslinks the collagen fibers of the dentin, thereby reconstructing the "scaffolding" that precipitates inorganic salts that make up tooth tissue, such as hydroxyapatite.
[0024] Calcium phosphate compounds (A) The dental hardenable calcium phosphate cement of the present invention contains a calcium phosphate compound (A) in the powder, which is the first material. The dental hardenable calcium phosphate cement of the present invention has excellent dentinal tubule sealing properties due to the use of the calcium phosphate compound (A). In addition, the dental hardenable calcium phosphate cement of the present invention has excellent mineral density recovery properties even for demineralized dentin with low mineral density due to the combination of the calcium phosphate compound (A) with other components.
[0025] The calcium phosphate compound (A) used in the present invention is not particularly limited, and examples thereof include tetracalcium phosphate (Ca4(PO4)2O; TTCP), anhydrous calcium hydrogen phosphate (CaHPO4; DCPA), anhydrous calcium dihydrogen phosphate (Ca(H2PO4)2), α-tricalcium phosphate (Ca3(PO4)2; α-TCP), β-tricalcium phosphate (Ca3(PO4)2; β-TCP), amorphous calcium phosphate (Ca3(PO4)2·nH2O, ACP), calcium pyrophosphate (CaH2P2O7), octacalcium phosphate (Ca8H2(PO4)6·5H2O), etc. The calcium phosphate compound (A) may be used alone or in combination of two or more kinds. A preferred embodiment includes a dental hardenable calcium phosphate cement, wherein the calcium phosphate compound (A) comprises tetracalcium phosphate and at least one selected from the group consisting of anhydrous calcium hydrogen phosphate (DCPA), anhydrous calcium dihydrogen phosphate (Ca(H2PO4)2), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), amorphous calcium phosphate (ACP), calcium pyrophosphate (CaH2P2O7), and octacalcium phosphate (Ca8H2(PO4)6·5H2O).
[0026] The calcium phosphate compound (A) is preferably in the form of particles. The average particle diameter of the calcium phosphate compound (A) is not particularly limited, but when the average particle diameter is 0.1 μm or more, calcium phosphate does not rapidly aggregate, so that no aggregation occurs during production and composition adjustment becomes easy. Therefore, the average particle diameter of the calcium phosphate compound (A) is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. On the other hand, when the average particle diameter of the calcium phosphate compound (A) is 40 μm or less, the paste obtained by mixing with the liquid, which is the second material described later, exhibits sufficient viscosity and has favorable paste properties. In addition, the roughness during paste kneading is reduced, and good operability can be maintained. Therefore, the average particle diameter of the calcium phosphate compound (A) is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less.
[0027] Here, the average particle size of each component, such as the calcium phosphate compound (A), the fluoride salt of a divalent or higher cation (B), and the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, used in the present invention, is measured and calculated using a laser diffraction particle size distribution analyzer ("SALD-2300" manufactured by Shimadzu Corporation). For example, it can be calculated by the method described in the Examples below.
[0028] The method for producing the calcium phosphate compound (A) used in the present invention is not particularly limited. A commercially available product may be used as it is, or may be used after being appropriately pulverized to adjust the particle size. When pulverizing a commercially available product, a pulverizing device such as a ball mill, a mortar and pestle machine, or a jet mill may be used. In addition, the calcium phosphate compound (A) may be obtained by pulverizing the raw material powder of the calcium phosphate compound (A) together with a liquid medium such as alcohol using a mortar and pestle machine, a ball mill, or the like to prepare a slurry, and drying the obtained slurry. In this case, it is preferable to use a ball mill as the pulverizing device, and alumina, zirconia, or the like is preferably used as the material of the pot and ball.
[0029] The content of the calcium phosphate compound (A) in the dental hardenable calcium phosphate cement of the present invention is not particularly limited, but is preferably 40 to 95 parts by mass, more preferably 45 to 90 parts by mass, and even more preferably 50 to 85 parts by mass, based on 100 parts by mass of the total amount of the first material of the dental hardenable calcium phosphate cement. When the content of the calcium phosphate compound (A) is 40 parts by mass or more, the dental hardenable calcium phosphate cement improves its dentinal tubule sealing ability. On the other hand, when the content of the calcium phosphate compound (A) is 80 parts by mass or less, the viscosity of the dental hardenable calcium phosphate cement falls within an appropriate range, and a paste with good handling properties can be obtained.
[0030] Fluoride salts of divalent or higher cations (B) The dental hardenable calcium phosphate cement of the present invention contains a fluoride salt (B) of a divalent or higher cation in the powder, which is the first material. Since the cation constituting the fluoride salt (B) is divalent or higher, when the cation is eluted into the inside of the dentinal tubule, it reacts with a polyvalent organic acid (C) that forms an insoluble salt with the divalent or higher cation inside the dentinal tubule, and can form an insoluble salt. The presence of the insoluble salt inside the dentinal tubule improves the dentinal tubule sealing ability. Furthermore, the dental hardenable calcium phosphate cement of the present invention contains a fluoride salt (B) of a divalent or higher cation, and when used in a ratio in a specified particle size distribution described below, the fluoride salt (B) penetrates into the dentinal tubules in the form of particles, and fluoride ions and divalent metal ions, which are essential components for mineral density recovery, are eluted from the particles that remain in the dentinal tubules into the interior of the dentinal tubules while remaining sufficiently within the dentinal tubules, thereby providing excellent mineral density recovery ability even for demineralized dentin with low mineral density.
[0031] The fluoride salt (B) of divalent or higher cations is not particularly limited, and examples thereof include zinc fluoride, strontium fluoride, magnesium fluoride, and titanium (IV) fluoride. The fluoride salt (B) of divalent or higher cations may be used alone or in combination of two or more. Among them, from the viewpoint of further improving the mineral density recovery ability, it is preferable to contain zinc fluoride and / or strontium fluoride, and it is more preferable to contain zinc fluoride and strontium fluoride. The cation constituting the fluoride salt (B) may be divalent or trivalent or higher.
[0032] The fluoride salt of a divalent or higher cation (B) is preferably in the form of particles. In view of its excellent ability to restore mineral density even to demineralized dentin, the cumulative frequency (proportion of cumulative particle size by volume) of particle sizes of 0 μm or more and 3 μm or less in the volume-based cumulative particle size distribution is 3% or more in the total amount of the fluoride salt (B) of a divalent or higher cation used in the present invention. When the cumulative frequency of particle diameters of 0 μm to 3 μm relative to the total particle diameter volume of the fluoride salt (B) is less than 3%, the fluoride salt (B) of divalent or higher cations cannot remain sufficiently in the dentinal tubules, and the mineral density recovery ability is insufficient. The cumulative frequency of particle diameters of 0 μm to 3 μm relative to the total particle diameter of the fluoride salt (B) of divalent or higher cations is 3% or more, and from the viewpoint of superior mineral density recovery ability for demineralized dentin, it is preferably 5% or more, more preferably 7% or more, even more preferably 10% or more, particularly preferably 20% or more, and most preferably 30% or more.
[0033] When a solution contains i types of fluoride salts (B) of divalent or higher cations (i is a positive integer of 1 or greater), each fluoride salt (B) of a divalent or higher cation is called (B) (1)、 (B) (2) (B) (i) In the volume-based cumulative particle size distribution, the cumulative frequency (%) of particles having a particle size of 0 μm or more and 3 μm or less relative to the total particle size volume of the fluoride salt (B) was calculated as follows:
[0034]
number
[0035] For example, when the fluoride salt of a divalent or higher cation (B) is zinc fluoride and strontium fluoride, the density of zinc fluoride (anhydrous) used in the above formula is 4.95 g / cm 3 The density of strontium fluoride used in the above formula is 4.24 g / cm 3 It is. The density of magnesium fluoride (MgF2) used in the above formula is 3.15 g / cm 3 The density of titanium(IV) fluoride used in the above formula is 2.8 g / cm 3 In the above formula, the true density of the compound of the fluoride salt of a divalent or higher cation (B) can be used.
[0036] The average particle diameter of the fluoride salt (B) of divalent or higher cations is not particularly limited, but when the average particle diameter is 0.1 μm or more, the fluoride salt (B) of divalent or higher cations does not rapidly aggregate, so that no aggregation occurs during production and composition adjustment becomes easy. Therefore, the average particle diameter of the fluoride salt (B) of divalent or higher cations is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. On the other hand, when the average particle diameter of the fluoride salt (B) of divalent or higher cations is less than 34 μm, the paste obtained by mixing with the liquid as the second material exhibits sufficient viscosity, resulting in a preferable paste property. In addition, the roughness during paste kneading is reduced, and good operability can be maintained. Therefore, the average particle size of the fluoride salt of a divalent or higher cation (B) is preferably less than 34 μm, and from the viewpoint of facilitating adjustment of the cumulative frequency of the particle size of 0 μm or more and 3 μm or less, it is more preferably 20 μm or less, and even more preferably 10 μm or less.
[0037] The method for producing the fluoride salt of divalent or higher cations (B) is not particularly limited. A commercially available product may be used as is, or may be used after being appropriately pulverized to adjust the particle size. When pulverizing a commercially available product, the same pulverization method as in the method for producing the calcium phosphate compound (A) can be used.
[0038] The content of the fluoride salt (B) of divalent or higher cations in the dental hardenable calcium phosphate cement of the present invention is preferably 0.6 to 40 parts by mass per 100 parts by mass of the total amount of the first material. When the content of the fluoride salt (B) of divalent cations is 0.6 part by mass or more, sufficient organic matter strengthening occurs, the ability to restore mineral density to demineralized dentin is obtained, and minerals are deposited in the demineralized dentin. The content of the fluoride salt (B) of divalent or higher cations is preferably 0.6 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 2.0 parts by mass or more, based on 100 parts by mass of the first material in total. On the other hand, when the content of the fluoride salt (B) of divalent or higher cations is 40 parts by mass or less, good dentinal tubule sealing properties can be obtained. The content of the fluoride salt (B) of divalent cations is preferably 40 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of the first material in total.
[0039] In the dental hardenable calcium phosphate cement of the present invention, when the first material:second material are mixed in a mass ratio of 1.6:1.0, the content of the fluoride salt (B) of a divalent or higher cation contained in the paste (powder-liquid mixture) after mixing is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, and particularly preferably 5 mass% or less, from the viewpoint of easily obtaining the ability to restore mineral density when the paste is applied to an affected area (e.g., demineralized dentin). The content of the fluoride salt (B) of a divalent or higher cation contained in the paste after kneading is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably 1.0 mass% or more.
[0040] Polyvalent organic acids (C) that form insoluble salts with divalent or higher cations The dental hardenable calcium phosphate cement of the present invention contains in the first material a polyvalent organic acid (C) that forms an insoluble salt with divalent or higher cations. By containing the polyvalent organic acid (C), collagen fibers in dentin are re-crosslinked, and the collagen decomposition inhibitory effect can be further enhanced, and by combining with other components, the ability to restore mineral density can be improved even in demineralized dentin.
[0041] The polyvalent organic acid (C) used in the present invention includes polyphenol compounds. The polyvalent organic acid (C) may be used alone or in combination of two or more. Examples of the polyphenol compounds include polyphenol compounds containing an aromatic ring having two or more hydroxyl groups, such as tannic acid, catechol, tiron monohydrate, protocatechuic acid, protocatechuic acid esters (methyl gallate, ethyl protocatechuate), pyrocatechol, pyrogallol, shikimic acid, gallic acid, gallic acid esters (methyl gallate, ethyl gallate, propyl gallate), epigallocatechin gallate (EGCG), and catechin. It is preferable that the mineral extract is at least one selected from the group consisting of catechol, tiron monohydrate, protocatechuic acid, protocatechuic acid esters (methyl protocatechuate, ethyl protocatechuate), pyrocatechol, pyrogallol, shikimic acid, gallic acid, gallic acid esters (methyl gallate, ethyl gallate, propyl gallate), and catechin, and tannic acid is particularly preferable because of its excellent ability to restore mineral density to demineralized dentin.
[0042] The polyvalent organic acid (C) is preferably in the form of particles. The average particle size of the polyvalent organic acid (C) is not particularly limited, but when the average particle size is 5.0 μm or more, the mineral density recovery ability for demineralized dentin is more excellent. Therefore, the average particle size of the polyvalent organic acid (C) is preferably 5.0 μm or more, more preferably 7.5 μm or more, and even more preferably 10 μm or more. On the other hand, when the average particle size of the polyvalent organic acid (C) is 100 μm or less, the roughness of the paste obtained by mixing with the second material liquid during kneading is reduced, and good operability can be maintained. Therefore, the average particle size of the polyvalent organic acid (C) is preferably 100 μm or less, and from the viewpoint of the excellent mineral density recovery ability for demineralized dentin, it is more preferable that it is 75 μm or less, and even more preferable that it is 40 μm or less. The polyvalent organic acid (C) may be water-soluble, and after being dissolved in water during paste preparation, may form an insoluble salt with the fluoride salt of a divalent or higher cation (B). Furthermore, since the polyvalent organic acid (C) dissolves to an extent that it can enter the dentinal tubules, the effects of the present invention can be achieved even if the particles have an average particle size that is large compared to the size of the dentinal tubules.
[0043] The method for producing the polyvalent organic acid (C) is not particularly limited. A commercially available product may be used as is, or may be used after being appropriately pulverized to adjust the particle size. When pulverizing a commercially available product, the same pulverization method as in the method for producing the calcium phosphate compound (A) may be used.
[0044] The content of the polyvalent organic acid (C) is preferably 0.1 to 25 parts by mass in 100 parts by mass of the total amount of the first material. When the content of the polyvalent organic acid (C) is 0.1 part by mass or more, sufficient organic matter strengthening occurs, the mineral density of the demineralized dentin is restored, and minerals are deposited in the demineralized dentin. The content of the polyvalent organic acid (C) is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the first material in total. On the other hand, when the content of the polyvalent organic acid (C) is 40 parts by mass or less, good dentinal tubule sealing properties are obtained. The content of the polyvalent organic acid (C) is preferably 25 parts by mass, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the first material in total.
[0045] ·Water (D) In the dental hardenable calcium phosphate cement of the present invention, the second material is a liquid containing water (D). In one embodiment, the second material is a liquid containing water (D) as a main component. The main component is a component with the largest content. The content of water (D) in the second material may be, for example, 50% by mass or more, 60% by mass or more, 70% by mass or more, or 100% by mass. The liquid containing water (D) as a main component may be a liquid containing water (D) as a main component and other solvents. The other solvents are not particularly limited, and include polyhydric alcohols such as glycerin, ethylene glycol, propylene glycol, and diglycerin; sugar alcohols such as xylitol, sorbitol, and erythritol; and polyethers such as polyethylene glycol and polypropylene glycol. The other solvents may be used alone or in combination of two or more.
[0046] ·pH adjustment material The dental hardenable calcium phosphate cement of the present invention may contain a pH adjusting material in at least one of the first material and the second material. The pH adjusting material is not particularly limited, and examples thereof include alkali metal salts of phosphoric acid such as disodium monohydrogen phosphate (Na2HPO4), dipotassium monohydrogen phosphate (K2HPO4), lithium dihydrogen phosphate (LiH2PO4), monosodium dihydrogen phosphate (NaH2PO4; MSP), monopotassium dihydrogen phosphate (KH2PO4; KDP), trisodium phosphate (Na3PO4; TSP), and tripotassium phosphate (K3PO4); hydroxides such as calcium hydroxide and sodium hydroxide, and the like. An alkali metal salt of phosphoric acid is preferable, a sodium salt of phosphoric acid is more preferable, and disodium monohydrogen phosphate is even more preferable.
[0047] The pH of the paste 30 seconds after mixing the first or second material is preferably 5.5 or more, more preferably 6.0 or more, and even more preferably 6.5 or more to prevent dissolution of teeth. The pH of the paste is preferably 14 or less, more preferably 12 or less, and even more preferably 10 or less. The pH adjusting agent can be used for the purpose of shortening the setting time and making the pH suitable for use in the oral cavity by adjusting the pH to the range of 6.5 to 10, where the solubility of hydroxyapatite (HAp) is lowest. Surprisingly, in a system containing a polyvalent organic acid (C) that forms insoluble salts with divalent or higher cations, the rate of HAp formation changes by adjusting the amount of pH adjuster added within a range that does not change the pH.
[0048] The pH adjuster is preferably in the form of particles. The average particle size of the pH adjuster is not particularly limited, but when the average particle size of the pH adjuster is 0.5 μm or more, no significant aggregation occurs, and the pH adjuster can be uniformly dispersed in the paste or powder, and when the dental hardenable calcium phosphate cement of the present invention is converted to hydroxyapatite, no holes are formed in the hydroxyapatite, and a high dentinal tubule occlusion rate can be maintained. Therefore, the average particle size of the particulate pH adjuster is preferably 0.5 μm or more, more preferably 4 μm or more, and even more preferably 8 μm or more. On the other hand, when the average particle size of the particulate pH adjuster is 20 μm or less, when the dental hardenable calcium phosphate cement of the present invention is converted to hydroxyapatite, no holes are formed in the hydroxyapatite, and a high dentinal tubule occlusion rate can be maintained, and hypersensitivity can be suppressed. Furthermore, when the pH adjuster is rubbed into the dentin surface to suppress dentin hypersensitivity, the increase in roughness and the decrease in operability due to the undissolved pH adjuster remaining in the paste can be prevented. Therefore, the average particle size of the pH adjuster is preferably 20 μm or less, more preferably 16 μm or less, and even more preferably 12 μm or less. The average particle size of the pH adjuster can be calculated by the same method as the method for measuring the average particle size of the calcium phosphate compound (A).
[0049] The method for producing the pH adjuster used in the present invention is not particularly limited. A commercially available product may be used as is, or the commercially available product may be appropriately pulverized to adjust the particle size before use. The pulverization method may be the same as that for the calcium phosphate compound (A).
[0050] Antibacterial The dental hardenable calcium phosphate cement of the present invention may contain an antibacterial agent in at least one of the first material and the second material in order to kill caries-causing bacteria that have infected inside the tooth substance. When the dental hardenable calcium phosphate cement of the present invention contains an antibacterial agent in its paste, if the antibacterial agent contains an antibacterial agent that is highly water-soluble, such as a cationic antibacterial agent or an anionic antibacterial agent, the antibacterial agent is easily eluted from the paste and exhibits antibacterial properties, making it possible to kill caries-causing bacteria inside the tooth structure. In one preferred embodiment, the second material includes a hardenable dental calcium phosphate cement that includes an antimicrobial agent.
[0051] As the antibacterial agent, various anionic, nonionic, cationic and amphoteric antibacterial agents can be used, and the anionic, nonionic and cationic antibacterial agents are preferred because they have the effect of inhibiting collagen decomposition. In addition, anionic antibacterial agents and cationic antibacterial agents are preferred because they are highly water-soluble and the sustained release of the antibacterial agent is easily controlled. As the antibacterial agent, cationic antibacterial agent containing quaternary ammonium salt compound is more preferred, and quaternary ammonium salt compound is even more preferred.As the quaternary ammonium salt compound, for example, benzalkonium chloride, cetylpyridinium chloride, benzethonium chloride, etc. can be mentioned.As the antibacterial agent, one kind can be used alone, or two or more kinds can be used in combination.
[0052] When an antibacterial agent is blended into the second material, the content of the antibacterial agent is preferably 0.0005 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.05 parts by mass or more, and particularly preferably 0.1 parts by mass, per 100 parts by mass of the total amount of the second material. When the content of the antibacterial agent is 0.0005 parts by mass or more, sufficient antibacterial properties are obtained. The content of the antibacterial agent in the second material is preferably 10 parts by mass or less, more preferably 5 parts by mass, and even more preferably 2.5 parts by mass. When the content of the antibacterial agent is 10 parts by mass or less, there are no problems such as cytotoxicity and genotoxicity, and the safety is excellent.
[0053] The dental hardenable calcium phosphate cement of the present invention is not particularly limited, and it is preferable to premix powders containing a calcium phosphate compound (A), a fluoride salt of a divalent or higher cation (B), and a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, which has the advantage of improving convenience without the need to measure each powder during clinical use. For the mixing, it is preferable to use a high-speed mixer, a V-type mixer, a laboratory mill, a touch mixer, a wonder crusher, a jet mill, a Raikai machine, a ball mill, a high-speed rotary mill, a planetary mill, a hybridizer, a mechanofusion, or a mixing extruder. In order to mix without causing excessive pulverization during mixing, it is preferable to use a high-speed mixer, a V-type mixer, a laboratory mill, a touch mixer, or a wonder crusher, and more preferable is a high-speed mixer or a V-type mixer.
[0054] In the dental hardenable calcium phosphate cement of the present invention, the calcium phosphate compound (A) dissolves in the presence of water and undergoes a reaction of gradually converting to hydroxyapatite, so the first material and the second material are mixed immediately before use. In addition, the dental hardenable calcium phosphate cement of the present invention is capable of precipitating hydroxyapatite deep within the dentinal tubules to seal them.
[0055] The dental hardenable calcium phosphate cement of the present invention is used in a paste state. The dental hardenable calcium phosphate cement of the present invention may be packaged as a product form. For example, the dental hardenable calcium phosphate cement of the present invention may be packaged as a kit product form in which the first material and the second material are combined.
[0056] The method for producing the dental hardenable calcium phosphate cement of the present invention is not particularly limited, and the components constituting the first material, which is a powder (calcium phosphate compound (A), fluoride salt of divalent or higher cation (B), polyvalent organic acid (C) that forms an insoluble salt with divalent or higher cation, and further optional components such as a pH adjuster and an antibacterial agent as necessary) can be mixed and packaged. In addition, the components constituting the second liquid material (water (D), and further other solvents, pH adjusters, antibacterial agents, etc., as necessary) can be mixed and packaged separately. The method for mixing the first material and the second material is not particularly limited, and known methods and devices can be used according to the form of the powder and liquid.
[0057] The dental hardenable calcium phosphate cement of the present invention can be used as a filling and restorative material, a lining material, a bonding material, a temporary sealing material, a root canal filling material, a temporary adhesive material, a coating material, a sealant material, a tooth surface treatment material, a dentifrice, a root caries treatment material, a dentin hypersensitivity suppressant, etc., which are used by filling cavities or defects in tooth structure, and is particularly suitable as a dentifrice, a tooth surface treatment material, a root caries treatment material, and a dentin hypersensitivity suppressant.
[0058] In the present invention, the mixing ratio of the first material (powder material) and the second material (liquid material) directly affects the operability during mixing, so it can be set based on the ratio of the first material to the second material. The mixing ratio of the first material to the second material is not particularly limited, but it is preferable that the mass ratio of the first material / second material is 1.1 or more because the consistency of the paste after mixing is not too loose, more preferably 1.2 or more, and even more preferably 1.3 or more. On the other hand, it is preferable that the mass ratio of the first material / second material is 2.1 or less because the consistency of the paste after mixing is not too hard, more preferably 2.0 or less, and even more preferably 1.9 or less.
[0059] The dental hardenable calcium phosphate cement of the present invention may contain other components than the calcium phosphate compound (A), the fluoride salt of a divalent or higher cation (B), the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, water (D), a pH adjuster, and an antibacterial agent, so long as the effect of the present invention is not impaired. Examples of the other components include various additives such as thickeners, sweeteners (artificial sweeteners, etc.), preservatives, foaming agents, moisturizers, and flavorings; lactam compounds having a lactam skeleton, either a γ-lactam skeleton, a δ-lactam skeleton, or an ε-lactam skeleton, and having an acidic group, carbodiimide compounds, and fluorine compounds other than the fluoride salt of a divalent or higher cation (B).
[0060] Specific examples of thickeners include carboxymethylcellulose, sodium carboxymethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, polyvinyl alcohol, poly-L-lysine, poly-L-lysine salts, starches other than cellulose, carrageenan, guar gum, xanthan gum, cellulose gum, pectin, pectin salts, chitin, chitosan and other polysaccharides; polyhydric alcohols such as glycerin, ethylene glycol, propylene glycol, diglycerin; sugar alcohols such as xylitol, sorbitol, erythritol; polyethers such as polyethylene glycol, polypropylene glycol; acidic polysaccharide esters such as propylene glycol alginate ester; proteins such as hyaluronic acid and its salts, collagen, gelatin and their derivatives; polyglutamic acid and its salts, polyaspartic acid and its salts, polystyrene sulfonic acid and its salts, polyacrylic acid polymers, or inorganic fillers such as light anhydrous silicic acid, metal oxides, etc. One type of thickener may be used alone, or two or more types may be used in combination. When a thickener is added to the paste, at least one selected from sodium carboxymethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and chitosan is preferred in terms of solubility in water and viscosity. The thickener may be added to the first material or the second material. When a thickener is added to the powder, it is preferred to add an inorganic filler, more preferred to add at least one type of particles selected from the group consisting of light anhydrous silicic acid and metal oxides having an average particle size of 0.002 to 20 μm, and even more preferred to add light anhydrous silicic acid particles having an average particle size of 0.002 to 20 μm.
[0061] Examples of sweeteners include aspartame, acesulfame potassium, licorice extract, saccharin, and artificial sweeteners such as saccharin sodium.
[0062] As the preservative, foaming agent, moisturizing agent, fragrance, and the like, known materials can be used without any particular limitation.
[0063] Examples of lactam compounds having a lactam skeleton, which is any one of a γ-lactam skeleton, a δ-lactam skeleton, and an ε-lactam skeleton, and having an acidic group include those described in WO 2013 / 047826. Specific examples of the lactam compound include pyrrolidone carboxylic acid (γ-lactam compound), 6-oxo-2-piperidine carboxylic acid (δ-lactam compound), and 3-(2-oxo-1-azepanyl)propanoic acid (ε-lactam compound) from the viewpoint of inhibiting collagen decomposition.
[0064] Examples of the carbodiimide compound include carbodiimide compounds having a cyclic structure and carbodiimide compounds not having a cyclic structure. The carbodiimide compound is preferably a carbodiimide compound having 5 to 30 carbon atoms, more preferably a carbodiimide compound having 6 to 28 carbon atoms, and even more preferably a carbodiimide compound having 7 to 25 carbon atoms. By using the carbodiimide compound, the effect of inhibiting the decomposition of collagen in dentin and promoting the remineralization of demineralized dentin is more excellent. Specific examples of carbodiimide compounds include 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride, N,N'-dicyclohexylcarbodiimide, 1,3-diisopropylcarbodiimide, 1-ethyl-3-tert-butylcarbodiimide, and 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho-p-toluenesulfonate.
[0065] Examples of fluorine compounds other than the fluoride salts of divalent or higher cations (B) include alkali metal fluorides such as sodium fluoride, potassium fluoride, ammonium fluoride, and lithium fluoride, and monofluorophosphates such as sodium monofluorophosphate (Na2FPO3), sodium monofluorophosphate, and potassium monofluorophosphate, because they can promote remineralization of dentin demineralized by the above-mentioned components.
[0066] Furthermore, the dental hardenable calcium phosphate cement of the present invention can be blended with any pharmacologically acceptable drug, etc. In addition to the above-mentioned antibacterial agents, the drugs that can be blended include, for example, disinfectants, anticancer drugs, antibiotics, blood circulation improving drugs such as actosin and PEG1, growth factors such as bFGF, PDGF and BMP, and cells that promote hard tissue formation, such as osteoblasts, odontoblasts, and further induced pluripotent stem (iPS) cells prepared by dedifferentiating differentiated cells such as undifferentiated bone marrow-derived stem cells, embryonic stem (ES) cells and fibroblasts through gene transfer, as well as cells differentiated from these.
[0067] In the present invention, a paste-like dental hardenable calcium phosphate cement can be obtained by kneading a powder containing a calcium phosphate compound (A), a fluoride salt of a divalent or higher cation (B), and a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, with a liquid containing water (D). This paste-like dental hardenable calcium phosphate cement containing water is preferably prepared by kneading immediately before use in a medical setting. The kneading operation is not particularly limited, and hand kneading, kneading using a static mixer, etc. are preferably adopted. The solvent other than water used in the second material is not particularly limited, and examples thereof include polyhydric alcohols such as glycerin, ethylene glycol, propylene glycol, and diglycerin; and polyethers such as polyethylene glycol and polypropylene glycol.
[0068] In addition, the dental hardenable calcium phosphate cement of the present invention can deposit hydroxyapatite deep into the dentinal tubules to seal them. Therefore, the dentin hypersensitivity inhibitor containing the dental hardenable calcium phosphate cement of the present invention can self-harden after a predetermined time and seal the dentin tubules. The dentin hypersensitivity inhibitor containing the dental hardenable calcium phosphate cement of the present invention has excellent biocompatibility, is less irritating to the skin, and is excellent in safety. Furthermore, after the dentin hypersensitivity inhibitor is rubbed into the dentin tubules, the excess paste can be easily removed by washing with water, and no special method of use is required, so that the dentin hypersensitivity inhibitor of the present invention is excellent in usability. The dentin hypersensitivity inhibitor of the present invention is not particularly limited and may contain known additives. Examples of known additives include the same ones as those exemplified in toothpaste.
[0069] The dental hardenable calcium phosphate cement of the present invention preferably has a dentinal tubule occlusion rate (%) of 70% or more, more preferably 75% or more, even more preferably 80% or more, particularly preferably 85% or more, and most preferably 90% or more. The method for measuring the dentinal tubule occlusion rate (%) is as described in the Examples section below.
[0070] Furthermore, the dental hardenable calcium phosphate cement of the present invention preferably has a mineral density recovery ability (%) for demineralized dentin of 22% or more, more preferably 23% or more, even more preferably 24% or more, particularly preferably 26% or more, and most preferably 27% or more. The method for measuring the mineral density recovery capacity (%) is as described in the Examples section below.
[0071] In another embodiment, the composition is composed of a first material which is a powder and a second material which is a liquid, and the first material contains a calcium phosphate compound (A) and a fluoride salt of a divalent or higher cation (B), The second material includes a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, and water (D); The dental hardenable calcium phosphate cement may be one in which the cumulative frequency of particle diameters of 0 μm to 3 μm in the cumulative particle diameter distribution based on volume is 3% or more in the total amount of the fluoride salt (B) of the divalent or higher cation. As described above, in a preferred embodiment of the present invention, the first material contains a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation. On the other hand, in the case where the quality of the product can be maintained, such as not causing coloring of the second material, in addition to blending the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation into the first material, or instead of blending it into the first material, the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation can be blended into the second material.
[0072] In another embodiment, the first material is a powder and the second material is a liquid. The dentinal tubule occlusion rate (%) is 70% or more, The present invention includes a dental hardenable calcium phosphate cement having a mineral density recovery capacity (%) of 22% or more for demineralized dentin. In the embodiment, the first material contains a calcium phosphate compound (A) and the second material contains water (D). In the embodiment, the first material and / or the second material contains a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation. In the embodiment, the first material contains a fluoride salt of a divalent or higher cation (B). EXAMPLES
[0073] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited thereto. The average particle size of each particle of the calcium phosphate compound (A), the fluoride salt of a divalent or higher cation (B), the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, and the pH adjuster was measured on a volume basis using a laser diffraction particle size distribution measuring device ("SALD-2300" manufactured by Shimadzu Corporation), and the median diameter (d 50 ) was taken as the average particle size.
[0074] [Preparation of calcium phosphate compound (A)] Preparation of Tetracalcium Phosphate The particles of tetracalcium phosphate used in this example (average particle diameter d 50 The crude tetracalcium phosphate (1.5 μm) was obtained by grinding crude tetracalcium phosphate prepared as follows. Commercially available anhydrous calcium hydrogen phosphate particles (Product No. 1430, JT Baker Chemical Co., NJ) and calcium carbonate (Product No. 1288, JT Baker Chemical Co., NJ) were added to water in an equimolar amount, stirred for 1 hour, filtered, and dried to obtain a cake-like equimolar mixture, which was then heated at 1500°C for 24 hours in an electric furnace (FUS732PB, Advantec Toyo Co., Ltd.) and then cooled to room temperature in a desiccator to prepare a tetracalcium phosphate mass. The mixture was then roughly crushed in a mortar and sieved to remove fine powder and tetracalcium phosphate masses, and the particle size was adjusted to the range of 0.5 to 1.0 mm to obtain crude tetracalcium phosphate. 50 g of this crude tetracalcium phosphate, 200 g of zirconia balls with a diameter of 10 mm, and 100 g of 99.5% dehydrated ethanol (FUJIFILM Wako Pure Chemical Industries, Ltd., "Ethanol, Dehydrated (99.5)") were added to a 1000 ml alumina grinding pot (Nikkato Corporation, "HD-B-104 Pot Mill") and subjected to wet vibration grinding at a rotation speed of 1500 rpm for 20 hours. The slurry obtained by distilling off the ethanol using a rotary evaporator was then vacuum-dried at 60°C for 6 hours to obtain tetracalcium phosphate particles (average particle diameter d 50 :1.5 μm) was obtained.
[0075] Preparation of anhydrous calcium phosphate The particles of anhydrous calcium hydrogen phosphate used in this example (average particle diameter d 5050 g of commercially available anhydrous calcium hydrogen phosphate particles (Product No. 1430, JT Baker Chemical Co., NJ, average particle size 10.2 μm), 240 g of 95% ethanol (FUJIFILM Wako Pure Chemical Industries, Ltd., "Ethanol (95)"), and 480 g of zirconia balls with a diameter of 10 mm were added to a 1000 ml alumina grinding pot (Nikkato Corporation, "HD-B-104 Pot Mill") and subjected to wet vibration grinding at a rotation speed of 1500 rpm for 15 hours. The slurry obtained by removing the ethanol with a rotary evaporator was then vacuum dried at 60 °C for 6 hours to obtain anhydrous calcium hydrogen phosphate particles (average particle size d 50 : 4.4 μm).
[0076] Preparation of α-tricalcium phosphate The particles of α-tricalcium phosphate used in this example (average particle diameter d 50 α-tricalcium phosphate particles (average particle diameter d: 3.2 μm) were obtained by adding 50 g of commercially available α-tricalcium phosphate particles (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 240 g of 95% ethanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., "Ethanol (95)"), and 480 g of zirconia balls with a diameter of 10 mm to a 1000 ml alumina grinding pot (manufactured by Nikkato Corporation, "HD-B-104 Pot Mill") and subjecting the resulting slurry to wet vibration grinding at a rotation speed of 1500 rpm for 1 hour. The ethanol was then removed using a rotary evaporator, and the slurry was then vacuum dried at 60 °C for 6 hours to obtain α-tricalcium phosphate particles (average particle diameter d 50 :3.2 μm).
[0077] [Preparation of fluoride salts of divalent or higher cations (B)] Zinc Fluoride Zinc fluoride (manufactured by Fluorochem, average particle size: 34 μm) was used as it is, or zinc fluoride (manufactured by Hakutatsu Chemical Laboratory, average particle size: 24 μm) was used as it is. Zinc fluoride (manufactured by Hakutatsu Chemical Laboratory Co., Ltd., average particle size: 24 μm) was pulverized in a lab mill (manufactured by Osaka Chemical Co., Ltd.) for 1 minute x 9 times to obtain zinc fluoride with an average particle size of 3 μm.
[0078] Strontium fluoride Strontium fluoride (manufactured by Hakutatsu Chemical Laboratory Co., Ltd., average particle size: 20 μm) was used as is. Strontium fluoride (manufactured by Hakutatsu Chemical Laboratory Co., Ltd., average particle size: 20 μm) was pulverized in a lab mill (manufactured by Osaka Chemical Co., Ltd.) for 1 minute x 9 times to obtain zinc fluoride with an average particle size of 3 μm.
[0079] [Evaluation of the cumulative frequency (%) of particle sizes between 0 μm and 3 μm in the volume-based cumulative particle size distribution in the total amount of fluoride salts of divalent or higher cations (B)] In the case where the fluoride salt (B) of a divalent or higher cation used in the examples and comparative examples contains i kinds (i is a positive integer of 1 or more), each fluoride salt (B) of a divalent or higher cation is (B) (1)、 (B) (2) (B) (i) In the volume-based cumulative particle size distribution, the ratio of the cumulative particle size volume of particles having a particle size of 0 μm or more and 3 μm or less to the total particle size of (B) was calculated as follows: In Examples 1 to 10 and 13 and Comparative Example 2, i=2, and in Examples 11 to 12 and Comparative Examples 1 and 4, i=1. The conditions for measuring the particle size distribution are shown below. Refractive index: Zinc fluoride 1.70-0.20i, Strontium fluoride 1.70-0.20i Cell type: Batch cell Dispersion medium: Ethanol Pretreatment: Touch mixer for 10 seconds, ultrasonic for 5 minutes
[0080]
number
[0081] [Preparation of polyvalent organic acids (C) that form insoluble salts with divalent or higher cations] Commercially available tannic acid (manufactured by Fuji Chemical Industry Co., Ltd., average particle size: 40 μm) was used as is. Commercially available tannic acid (manufactured by Fuji Chemical Industry Co., Ltd., average particle size: 40 μm) was ground for 15 seconds in a lab mill (manufactured by Osaka Chemical Co., Ltd.) to obtain tannic acid with an average particle size of 40 μm. Tannic acid with an average particle size of 5 μm was obtained by grinding the mixture 9 times for 1 minute in a lab mill (manufactured by Osaka Chemical Co., Ltd.).
[0082] [pH adjustment material] Commercially available disodium monohydrogen phosphate (manufactured by Taihei Chemical Industry Co., Ltd., average particle size: 1.5 μm) was used as is.
[0083] [Inorganic filler] Commercially available light anhydrous silicic acid (Aerosil (registered trademark) 130, average particle size: 16 μm, manufactured by Nippon Aerosil Co., Ltd.) was used as is.
[0084] [Water(D)] Purified water was used as received.
[0085] [Antibacterial agents] Cetylpyridinium chloride anhydrous (Fujifilm Wako Pure Chemical Industries, Ltd.) was used as is.
[0086] [Preparation of dental hardenable calcium phosphate cement] <Examples 1 to 13 and Comparative Examples 1 to 4> (1) Preparation of the first material (powder) The components, such as calcium phosphate compound (A), fluoride salt of divalent or higher cation (B), and polyvalent organic acid (C) that forms insoluble salts with divalent or higher cations, were weighed out according to the compositions shown in Tables 1 and 2 and mixed in a Wonder Crusher (manufactured by Osaka Chemical Co., Ltd.) at 3,500 rpm for 10 minutes to obtain the first material, a powder material.
[0087] (2) Preparation of the second material (liquid) The antibacterial agent, weighed out according to the composition shown in Tables 1 and 2, was added to water (D) and stirred until dissolved, to obtain a liquid that was the second material.
[0088] (3) Preparation of dental hardenable calcium phosphate cement paste The dental settable calcium phosphate cement was prepared by mixing the first and second materials in a mass ratio of 1.6:1.0 for 30 seconds just before use. The composition of the obtained dental settable calcium phosphate cement is shown in Tables 1 and 2.
[0089] [Evaluation of dentinal tubule occlusion] (1) Preparation of bovine teeth for evaluating dentinal tubule occlusion The buccal center of a healthy bovine incisor was polished and trimmed with a rotary polisher using #80 and #1000 abrasive paper to prepare a dentin plate with a thickness of 2 mm with exposed buccal dentin. The buccal dentin surface was further polished and smoothed using lapping films (#1200, #3000, #8000, manufactured by Sumitomo 3M Limited). Test windows of 2 mm each in the longitudinal and transverse directions of the tooth were left in the buccal dentin portion. The bovine tooth was immersed in a 3% EDTA solution and exposed to ultrasonic waves for 10 minutes to demineralize the dentin window, and then washed with water to prepare the bovine tooth for use in the evaluation of dentinal tubule occlusion. A sufficient amount of the dental hardenable calcium phosphate cement paste of the present invention prepared as described above was applied to the buccal dentin surface of the bovine tooth, and the paste was rubbed into the entire dentin window for 30 seconds using a microbrush (MICROBRUSH INTERNATIONAL "REGULAR SIZE (2.0 mm), MRB400"). After that, the paste on the dentin surface was removed with distilled water (n=3).
[0090] (2) Preparation of samples for SEM observation After the above treatment, the bovine teeth were dried with an air blower to prepare samples for dentinal tubule observation.
[0091] (3) SEM Observation An SU-3500 (Hitachi High-Technologies Corporation) was used for SEM observation. The accelerating voltage was set at 5 kV, and the morphology of the dentin surface before application of dental hardenable calcium phosphate cement paste and the bovine tooth surface after application of the paste were observed (n=3). Three random points were observed for each SEM observation sample, and the dentinal tubule occlusion rate is expressed by the following formula. The average dentinal tubule occlusion rate of the three points was calculated. The results are shown in Tables 1 and 2. Dentinal tubule occlusion rate (%) = occluded dentinal tubules (number) / observed dentinal tubules (number) × 100
[0092] [Evaluation of mineral density recovery ability] The ability to promote remineralization of demineralized dentin was evaluated as mineral density recovery ability using the following method. (1) Preparation of decalcification solution A 50 mM aqueous solution of acetic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) and a 50 mM aqueous solution of sodium acetate trihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and adjusted to pH 4.5.
[0093] (2) Preparation of artificial saliva 87.6 mg of sodium chloride (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 122 mg of potassium dihydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 166 mg of calcium chloride (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 477 mg of 2-[4-(2-hydroxyethyl)-1-piperazinyl]ethanesulfonic acid (HEPES) (manufactured by Dojindo Laboratories, Inc.) were dissolved in approximately 800 mL of water, the pH was adjusted to 7.0 with a saturated aqueous solution of NaOH (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and the solution was diluted to 1.0 L.
[0094] (3) Reagents used to prepare test specimens The following compounds were used as reagents for preparing the test pieces. Ethanol: Kanto Chemical Co., Ltd. Propylene oxide: Fujifilm Wako Pure Chemical Industries, Ltd. Epoxy resin base: (Epocure 2 base, manufactured by Buehler) Hardener (Epocure 2 hardener, manufactured by BUEHLER)
[0095] (4) Preparation of test specimens Test specimens were prepared using the cervical part of bovine teeth. The surface of the cervical part of the bovine tooth was polished with #80 abrasive paper to expose the dentin, and then further polished with #1000 abrasive paper and ultrasonically treated for 5 minutes. A test window of approximately 5 mm x 2 mm was created on part of the surface of the cervical part of the bovine tooth, and the cervical part of the bovine tooth was divided into two halves symmetrically about the divided surface using a diamond cutter (Isomet 1000, manufactured by Buehler). Nail polish was applied to the areas of both of the divided test pieces other than the test window, and two test pieces were created, each with a 5mm x 1mm test window. Both test pieces were immersed in a decalcifying solution and decalcified at 37°C for two weeks. From the start of immersion in the decalcifying solution, the decalcifying solution was replaced once every three days.
[0096] One of the test windows (Test Window A) was painted with nail polish and allowed to dry. The test window (test window B) of the other test piece was rubbed with a sample (dental hardenable calcium phosphate cement of each Example and Comparative Example) for 30 seconds. After that, both test pieces were stored in a thermo-hygrostat at 37°C and 95% RH for 30 minutes. After the storage, the test piece was immersed in artificial saliva, and the artificial saliva was replaced five times within 7 days from the start of immersion, and then stored at 37°C for 2 weeks.
[0097] The nail polish was removed from the test pieces, and they were immersed in 70% ethanol, 80% ethanol, 90% ethanol, 99% ethanol, and 100% ethanol for 10 minutes each, and then in 100% ethanol for 1 day. They were immersed in a propylene oxide / ethanol = 1 / 1 mixture and propylene oxide for 10 minutes each, and then in propylene oxide for 1 day. They were immersed in an epoxy resin base / propylene oxide = 1 / 1 mixture, epoxy resin base / propylene oxide = 4 / 1, and epoxy resin base for 2 hours each, and then in an epoxy resin base / hardener = 4 / 1 mixture, and kept immersed at 60°C for 1 day to harden. The cured test pieces were cut perpendicular to the long sides of the test window with a diamond cutter (Isomet 1000, manufactured by Buehler) to a thickness of approximately 1.2 mm, and wrapping film (#1200, #3000, #8000, manufactured by 3M Japan Ltd.) was used to reduce the thickness of the test pieces to 0.060 mm to 0.110 mm.
[0098] (5)CMR(Contact Micro Radiography) For both test pieces obtained, a soft X-ray inspection device (product name "CMR-2", manufactured by Softex Co., Ltd.) and a glass dry plate (HIGH PRECISION PHOTO PLATE HPP-SN2 2x2, manufactured by Konica Minolta, Inc.) were used to photograph the entire test piece at a tube voltage of 10 kV, a tube current of 2.0 mA, and an exposure time of 10 minutes. The photographed test piece (dry plate) was immersed in a developer (medical X-ray liquid developer "Hilendol", Fujifilm Co., Ltd.) for 5 minutes, washed with distilled water for 1 minute, immersed in a fixer (fixer "Hilenfix", Fujifilm Co., Ltd.) for 5 minutes, and washed with distilled water for 30 seconds.
[0099] (6) Analysis The obtained CMR images were photographed with a microscope (Nikon DS-Ri1, manufactured by Nikon Solutions Corporation), and the brightness value was measured from the surface of the test window in the depth direction of the test window (n=3) using image analysis software (ImageJ, open source, public domain) with the brightness value at 100 μm directly below the nail polish protection of the undecalcified part as the standard, and the mineral density recovery ability (%) was calculated using the following formula: In each of the following formulas, "control" means the case where no treatment was performed with the sample (dental hardenable calcium phosphate cement of each Example and Comparative Example).
[0100] Control mineral density at any depth = Control brightness value at any depth / brightness value 100μm below the nail polish protection of the undecalcified part
[0101] Treatment surface mineral density at any depth = Luminance value of treated surface at any depth / Luminance value 100μm directly below nail polish protection of undecalcified part
[0102] The measurement interval was set to 7 μm for the range from 7 μm to 497 μm, and the calculation was performed using the following method.
number
[0103] [Table 1]
[0104] [Table 2]
[0105] As is clear from the above results, it was confirmed that the dental hardenable calcium phosphate cements of the present invention (Examples 1 to 13) have excellent dentinal tubule sealing properties and also have a high ability to restore mineral density to demineralized dentin.
[0106] In contrast, Comparative Example 1, which used a fluoride salt of a divalent or higher cation in which the cumulative frequency (%) of particle diameters of 0 μm or more and 3 μm or less in the volume-based cumulative particle size distribution was less than 3% in the total amount of the fluoride salt of a divalent or higher cation (B), had insufficient mineral density recovery ability.
[0107] Comparative Example 2, which did not contain calcium phosphate powder, did not become a paste, had no dentinal tubule sealing ability, and did not remain in the tooth structure, so mineral density recovery ability could not be confirmed. Comparative Examples 3 and 4, which did not contain sufficient amounts of fluoride salt (B) of a divalent or higher cation and polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation, had insufficient mineral density recovery ability. [Industrial Applicability]
[0108] The dental hardenable calcium phosphate cement according to the present invention is suitably used in the field of dentistry as a tooth surface treatment material (for example, a material for suppressing dentin hypersensitivity, a material for treating root caries, etc.) and a toothpaste.
Claims
1. It is composed of a first material which is a powder and a second material which is a liquid. The first material includes a calcium phosphate compound (A), a fluoride salt of a divalent or higher cation (B), and a polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation; The second material contains water (D), A dental hardenable calcium phosphate cement, in which the cumulative frequency of particle diameters of 0 μm or more and 3 μm or less in a volume-based cumulative particle diameter distribution is 3% or more in the total amount of the fluoride salt of a divalent or higher cation (B).
2. 2. The dental hardenable calcium phosphate cement of claim 1, wherein the fluoride salt (B) is zinc fluoride and strontium fluoride.
3. 3. The dental hardenable calcium phosphate cement according to claim 1, wherein the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation is at least one selected from the group consisting of tannic acid, catechol, tiron monohydrate, protocatechuic acid, protocatechuic acid esters, pyrocatechol, pyrogallol, shikimic acid, gallic acid esters, and catechin.
4. 3. The dental hardenable calcium phosphate cement according to claim 1, wherein the average particle size of the fluoride salt of a divalent or higher cation (B) is less than 34 μm.
5. The calcium phosphate compound (A) is selected from the group consisting of tetracalcium phosphate, anhydrous calcium hydrogen phosphate (CaHPO 4 ), anhydrous calcium dihydrogen phosphate (Ca(H 2 P.O. 4 ) 2 ), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), amorphous calcium phosphate (Ca 3 (P.O. 4 ) 2 ・nH 2 O), calcium pyrophosphate (CaH 2 P 2 O 7), octacalcium phosphate (Ca 8 H 2 (P.O. 4 ) 6 ・5H 2 O), calcium hydrogen phosphate dihydrate (CaHPO 4 ・2H 2 O), and calcium dihydrogen phosphate monohydrate (Ca(H 2 P.O. 4 ) 2 ・H 2 3. The dental hardenable calcium phosphate cement according to claim 1, further comprising at least one selected from the group consisting of:
6. The dental hardenable calcium phosphate cement according to claim 1 or 2, wherein the first material or the second material further comprises a pH adjuster.
7. 7. The dental hardenable calcium phosphate cement according to claim 6, wherein the pH adjuster is an alkali metal salt of phosphoric acid.
8. The dental hardenable calcium phosphate cement according to claim 1 or 2, wherein the first material or the second material further comprises an inorganic filler.
9. 9. The dental hardenable calcium phosphate cement according to claim 8, wherein the inorganic filler comprises at least one selected from the group consisting of light anhydrous silicic acid and metal oxides.
10. The dental hardenable calcium phosphate cement of claim 1 or 2, wherein the second material further comprises an antibacterial agent.
11. 3. The dental hardenable calcium phosphate cement according to claim 1, wherein the calcium phosphate compound (A) is in the form of particles having an average particle size of 0.1 to 40 μm.
12. 3. The dental hardenable calcium phosphate cement according to claim 1, wherein the polyvalent organic acid (C) that forms an insoluble salt with a divalent or higher cation is in the form of particles having an average particle size of 5.0 to 100 μm.
13. A tooth surface treatment material comprising the dental hardenable calcium phosphate cement according to claim 1 or 2.
14. A material for suppressing dentin hypersensitivity, comprising the dental hardenable calcium phosphate cement according to claim 1 or 2.
15. A dentifrice comprising the dental hardenable calcium phosphate cement according to claim 1 or 2.
16. A root caries treatment material comprising the dental hardenable calcium phosphate cement according to claim 1 or 2.
